Targeting neuroplasticity: a viewpoint on a future research direction with Parkinson’s disease-related fatigue - Hao, Shijie; Zou, Jianpeng (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease-related fatigue has an insidious onset and complex pathomechanisms, causing many adverse effects on patients. In clinical practice, Parkinson’s disease-related fatigue has not received sufficient attention, and its early diagnosis and targeted interventions are inadequate. Currently, pharmacological treatments for Parkinson’s disease-related fatigue have limited efficacy and nonpharmacological therapies such as non-invasive brain stimulation techniques and exercise therapy have been shown to have a role in improving Parkinson’s disease-related fatigue. Further studies have revealed that modulation of functional cortical excitability, induction of neuroplasticity changes, inhibition of oxidative stress, improvement of cardiorespiratory fitness, and enhancement of muscle strength may be potential mechanisms of action of non-pharmacological therapies. As relevant research continues to progress, targeted therapy based on the theory of neuroplasticity may become an important therapeutic idea for Parkinson’s disease-related fatigue. This article provides an overview of the diagnosis, etiology, and treatment of Parkinson’s disease-related fatigue, and on this basis proposes a new diagnostic and therapeutic idea of targeting neuroplasticity to improve Parkinson’s disease-related fatigue for clinical reference. Further studies on the pathological mechanisms of Parkinson’s disease-related fatigue are needed in the future to optimize the treatment regimen of Parkinson’s disease-related fatigue to improve the efficacy of treatment for the benefit of patients.